A portable device for in situ deposition of bioproducts. Issue 2 (June 2014) - Lau, Wai K.; Sofokleous, Panagiotis; Day, Richard; Stride, Eleanor; Edirisinghe, Mohan
Abstract : The electrohydrodynamic (EHD) technique has traditionally been confined to the bench-top. Recently, a portable EHD device was constructed that allows the process to be applied in a much more flexible and versatile manner. In this article, the effect of electrode and collector height on the fibers generated by EHD and wound-dressing forming capabilities of the device tested on different types of simulated wound morphologies were investigated. Dressings were also fabricated on living tissue to investigate jet behavior and product morphology. The EHD device was found to be capable of controlled deposition of micrometer-sized poly(D, L-lactide-co-glycolide) acid fibers that can form an opaque, waterproof wound dressing on human skin within a few minutes with excellent adherence.